The hierarchical analytical process as a methodology for selecting scientific journals in the biotechnology area - Márquez Benavides, Liliana (2017)
The aim of this study is to establish an applicable methodology for the selection of a journal when aspiring to publish a scientific work in the biotechnology field, using the hierarchical analytical process. The publication of papers in indexed journals is one of the main goals of scientific research work. That’s why it is of great importance to select the journal that best disseminates the information of the paper among the technical-scientific community; however, having to rely on subjective criteria in the journal selection process can result in time and energy waste, unnecessary costs and a low dissemination of the researcher's scientific productivity. To establish the methodology, 11 qualitative and quantitative parameters of 20 scientific journals were evaluated, validated by a group of experts in the area, followed by a hierarchical analysis process, which established the selection criteria. It was found that the key elements to consider the journal selection are the impact factor, the acceptance time, the type of indexing and the number of articles published by the journal. Thus, with a methodology to choose the appropriate journal, it is possible to increase the possibilities of publishing the article, decrease the waiting time, publication costs and achieve a larger number of citations once published, using a variety of criteria and not just bibliometric criteria as the impact factor.